ANALISIS GANGGUAN PADA KWH METER PELANGGAN DI PT. PLN (PERSERO) UP3 SUMBAWA MENGGUNAKAN FISHBONE DAN PDCA (PLAN, DO, CHECK, ACTION) - Yuniar Adekayanti; Iksan Adiasa; Ismi Mashabai (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2021)
Along with the rapid development of technology in the industrial world, the need for electrical energy is also increasing. PT. PLN (Persero) UP3 Sumbawa is a state-owned company (BUMN) that helps provide and deal with various electricity problems in the surrounding area. Steps taken by this company in maintaining the safety and comfort of using electrical energy is to carry out regular checks at the customer's home. However, this step is deemed ineffective because the customer may not be at home during the checking. In addition, checking manually can also cause errors when recording the KWH meter, so that this can cause losses to the customer and the company. Therefore, PT. PLN (Persero) introduced a new system, namely the Automatic MeterReading (AMR) system. With this system, companies can read KWH meters remotely and automatically so that there are no more errors in recording KWH meters. However, the use of the system must be balanced with a good communication network. Several areas in Sumbawa still have difficulties in accessing the communication network, causing several disturbances to occur in the system. With the existence of various previous problems, a research was conducted to observe the types of disturbances as well as efforts to prevent and deal with disturbances in the KWH Meter system at PT. PLN (Persero) UP3 Sumbawa uses the Fishbone and PDCA (Plan, Do, Check, Action) methods.